PECULIARITIES OF MODIFYING OF MALLEABLE IRON BY BISMUTH-MOLYBDENIC CATALYST - N. I. Urbanovich; O. S. Komarov; I. V. Provorova; V. M. Priemko (Литьë и металлургия)
The peculiarities of annealed cast iron modifying by bismuth-molybdenic catalyst are shown.